2008
DOI: 10.3164/jcbn.2008030
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Ulcer Healing and Resistance to Ulcer Recurrence with Gastroprotectants in Rat Model of Acetic Acid-induced Gastric Ulcer

Abstract: Summary Quality of ulcer healing (QOUH) is defined as ideal ulcer healing featuring with the fine granular ulcer scar, high functional restoration and the resistance to recurrence. This study was designed to compare the rates of QOUH achievement in rat gastric ulcer model between acid suppressant treated group and gastroprotectant treated group accompanied with elucidations of molecular mechanisms. Serosal injection of acetic acids for generating gastric ulcer and intraperitoneal (ip) injection of recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Groups II, III, and IV were then treated with mice recombinant human interleukin-1β (IL-1β; 200 μg/kg) respectively for 48 h from day 7 to induce the recurrence of colitis according to the method reported previously with modifications. [ 18 , 19 ] IL-1β produced by inflammatory cells has various biological activities. Infiltrating neutrophils recruited by adhesion molecules are up-regulated by IL-1β, which is closely related to the recurrence of colitis.…”
Section: Methodsmentioning
confidence: 99%
“…Groups II, III, and IV were then treated with mice recombinant human interleukin-1β (IL-1β; 200 μg/kg) respectively for 48 h from day 7 to induce the recurrence of colitis according to the method reported previously with modifications. [ 18 , 19 ] IL-1β produced by inflammatory cells has various biological activities. Infiltrating neutrophils recruited by adhesion molecules are up-regulated by IL-1β, which is closely related to the recurrence of colitis.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical studies were then performed using full thickness of intestinal wall in the distal colonic samples. The study of colitis recurrence was conducted according to the methods reported previously with modifications (Watanabe et al, 1997 ; Young Oh et al, 2008 ). Briefly, the recurrence of colitis after SASP or Sal B treatment was induced by giving rats recombinant human IL-1β (150 μg/kg) intraperitoneally for 48 h from day 15.…”
Section: Methodsmentioning
confidence: 99%
“… 5 The gastric mucosa is exposed to acid and other chemical hazards, including food intake, assuming that there is a high chance to receive several challenges during ulcer healing. In the acetic acid–induced ulcer rodent model, several reports have shown that administration of nonsteroidal anti-inflammatory drugs or H pylori causes an ulcer in the area where the initial ulcer had healed, 10 , 39 , 40 although why an offense-induced relapse ulcer occurs at the same site or near the site still is unknown. In the present study, we observed that H pylori causes ulcer relapse, specifically at the site of visually healed regenerated epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in rodents observed prominent histologic and structural abnormalities in visually healed tissue at least 28 weeks after ulcer induction, including poor differentiation and/or degenerative changes in glandular cells, increased connective tissue, and disorganized microvascular arrays. 1 , 3 , 10 Moreover, in the gastric glands of healed ulcer tissue an up-regulation of trefoil factor 2 (TFF2) and mucin (MUC)6 is accompanied by a lack of parietal cells, 11 , 12 similar to the metaplastic state identified as a precursor of gastric cancer. 12 , 13 , 14 Interestingly, mice with genetic disruption of the Na/H exchanger isoform sodium hydrogen exchanger 2 (NHE2) have atrophied parietal cells with up-regulation of TFF2, 15 , 16 and it has been shown that NHE2 is a downstream mediator of TFF2 for the gastric repair of damage.…”
mentioning
confidence: 99%